Extended Spectrum β-Lactamase Producers in Mobile Phones and Nosocomial infections: Risk Factors for Infection Control Practices - Sharma, Binita Koirala; Sharma, Keshab (Janapriya Journal of Interdisciplinary Studies, 2019)
Extended Spectrum β-Lactamase Producers (ESBLs) isolates contaminating the healthcare workers (HCWs)mobile phones may cause threat to not only the life of hospital staffs, patients and visitors but also to the people in the community. This study was conducted to determine whether mobile phones of HCWs harbor ESBLs with their antibiotic susceptibility pattern. Isolation, identification and antimicrobial susceptibility test of bacteria were done using standard microbiological procedures. Further screening and confirmation of ESBLs were done according to Clinical Laboratory Standard Institutes (CLSI) guidelines. Out of the 100mobile swab samples cultured, 97 (97%) showed bacterial growth. Frequency distribution of the total 67isolates showed that the most prevalent Gram negative bacteria identified was Klebsiella spp 29.85%,followed by Escherichia coli 22.38%, Acenetobacter spp 14.93%, Proteus spp 13.43%, Pseudomonasaeruginosa 8.96%, Enterobacter spp 7.46% and Citrobacter spp 2.99%. The prevalence of ESBLs among the Gram negative isolates in this study was 29.85%. The most effective drug of choice were Amikacin, Nitro furantoin and Imipenem for many gram negative isolates. These results showed that HCWs' mobile phones were contaminated with various types of pathogenic multi drug resistant microorganisms. Mobile phones used by HCWs in daily practice may be a source of hospital acquired infections in hospitals. Indeed, HCWs mobile phones contaminated with ESBLs increase the risk for infection may be the key factor in epidemiology of ESBLs producing bacterial infection not only in a hospital setting but also in community. Therefore, regular surveillance, disinfection with suitable agent at regular interval would minimize the colonization and transmission of pathogens like ESBLs.